Leadership on the line : Staying alive through the dangers of leading - Heifetz, Ronald A (Boston, 2002)
To lead is to live dangerously. It's romantic and exciting to think of leadership as all inspiration, decisive action, and rich rewards, but leading requires taking risks that can jeopardize your career and your personal life. It requires putting yourself on the line, disturbing the status quo, and surfacing hidden conflict. And when people resist and push back, there's a strong temptation to play it safe. Those who choose to lead plunge in, take the risks, and sometimes get burned. But it doesn't have to be that way say renowned leadership authorities Ronald Heifetz and Marty Linsky. In Leadership on the Line, they show how it's possible to make a difference without getting "taken out" or pushed aside. They present everyday tools that give equal weight to the dangerous work of leading change and the critical importance of personal survival. Through vivid stories from all walks of life, the authors present straightforward strategies for navigating the perilous straits of leadership. Whether parent or politician, CEO or community activist, this practical book shows how you can exercise leadership and survive and thrive to enjoy the fruits of your labor.
Keywords: Leadership